Ciliated cell damage in the bronchial epithelium of asthmatics and non-asthmatics - MONTEFORT, S.; DJUKANOVIĆ, R.; HOLGATE, S. T.; ROCHE, W. R. (Clinical and experimental allergy, 1993)
Summary The importance of bronchial epithelial shedding in the pathogenesis of asthma has been highlighted by many investigators as a potential mechanism for bronchial hyperresponsiveness. It has been suggested that this disruption is the result of cytotoxic injury leading to shedding of damaged cells. To investigate whether damaged ciliated epithelial cells can be detected within the bronchial mucosa. we used tannic acid which only permeates disrupted cellular membranes, as a marker of cell damage. Bronchial biopsies from seven asthmatic and six normal subjects, were processed in tannic acid prior to preparation and sectioning for electronmicroscopic examination. Ciliated epithelial cells staining darkly with tannic acid were seen to comprise a similar proportion of the intact portion of bronchial epithelium in both normals and asthmatics (medians 31% vs 40%). We suggest that ciliated epithelial cells are not shed from the bronchial mucosa immediately after damage and that mechanisms other than granulocyte‐mediated cytotoxicity may account for epithelial disruption in asthma, possibly involving the selective damage or reduced expression of intraepilhelial intercellular adhesion molecules.